Analysis of downregulated salivary proteins in oral submucous fibrosis - A quantitative proteomic pilot study - Anu Babu; Laxmikanth Chatra; Prashanth Shenoy (Wolters Kluwer Medknow Publications, 2021)
Background: Oral submucous fibrosis (OSMF) is a chronic debilitating disease of the oral cavity which is strongly associated with chewing of areca nut. The rate of malignant transformation varies between 3% and 19%. As oral lesions are in direct contact with saliva, the altered composition of saliva has shown promising results in surveillance of malignant transformation. Aim: To do quantitative proteomic profiling of saliva in OSMF and to study the downregulated proteins. Methodology: Quantitative proteomic profiling was carried out using Liquid chromatography with Tandem mass spectroscopy (LC-MS/MS) on saliva obtained from patients with OSMF. Results: A total of 172 proteins were identified in saliva samples. Five proteins were downregulated in the samples (fold change average of disease vs. control ratio ≤0.6). Conclusion: Downregulated proteins could serve as potential biomarkers in the early detection of malignant transformation in OSMF.